The big bad world of concept art for video games : an insider's guide for students - Lilly, Eliott (Culver City, CA : Design Studio Press, 2015)
This is a comprehensive book that gives aspiring artists an honest, informative, and concise look at what it takes to become a concept artist in the video game industry. Author Eliott Lilly uses his own student work as a teaching tool along with personal experiences to help you on your journey. From finding the right school and getting the most out of your education, to preparing your portfolio and landing your first job, the advice and strategies Eliott offers are organized for easy reference and review. The book also features an extensive list of resources that students will find useful, as well as interviews with renowned concept artists David Levy, Sparth, Stephan Martiniere, Ben Mauro, and Farzad Varahramyan, all offering their own invaluable advice.
01. Getting started -- 02. Building a portfolio -- 03. Understanding the industry -- 04. Promoting yourself -- 05. The job hunt -- 05B. Applying for a job -- 06. The job interview -- 07. Negotiating your salary -- 08. When things go wrong -- 09. Sustaining your career -- 10. Recommended resources.
Includes bibliographical references (pages 138-139) and index.
Keywords: Computer games -- Design; Video games -- Design; Video games industry; Conceptual art